Acinetobacter baumannii producing OXA-23 detected in the Czech Republic - Senkyrikova, Marketa; Husickova, Vendula; Chroma, Magdalena; Sauer, Pavel; Bardon, Jan; Kolar, Milan (SpringerPlus, 2013)
BACKGROUND: Acinetobacter baumannii is an opportunistic pathogen posing an increased risk to hospitalized persons, causing nosocomial pneumonias, urinary tract infections and postoperative infections. METHODS: Between 1 December 2011 and 30 September 2012, strains of Acinetobacter spp. were isolated from clinical samples obtained from hospitalized patients. Susceptibility to antibiotics was determined by the standard microdilution method and phenotypic testing was used to detect the presence of serine carbapenemases and metallo-beta-lactamases. The polymerase chain reaction was used to detect the genes encoding carbapenemases. Pulsed field gel electrophoresis was used to investigate the genetic relationship among the carbapenem resistant isolates of Acinetobacter baumannii. RESULTS: In three strains of Acinetobacter baumannii enzyme OXA-23 was detected. This positive result was confirmed by restriction analysis and sequencing. The study reported an OXA-23-producing strains of Acinetobacter baumannii in the Czech Republic. All three strains isolated from Military Hospital patients had a completely identical restriction profile, indicating clonal spread of a strain carrying serine carbapenemase OXA-23 in this health care facility. Moreover this was the first time the strain was detected in the country in patients who had not stayed abroad.